2004
DOI: 10.1038/oby.2004.233
|View full text |Cite
|
Sign up to set email alerts
|

Energy Intake and Meal Portions: Associations with BMI Percentile in U.S. Children

Abstract: were averaged, and children were categorized into three age groups: 3 to 5 years (n ϭ 1077), 6 to 11 years (n ϭ 537), and 12 to 19 years (n ϭ 381). Physiologically implausible reports due to reporting bias or abnormal intake (rEI outside Ϯ18% to 23% of predicted energy requirements; pER) were identified. Results: rEI averaged 109 Ϯ 34% and 100 Ϯ 10% of pER in the total and plausible samples, respectively. EI was overreported more in younger children and underreported more in overweight older children. Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
243
3
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(268 citation statements)
references
References 42 publications
17
243
3
5
Order By: Relevance
“…[67][68][69] In our previous analyses, we showed that including only plausible reports resulted in stronger relationships of both eating patterns and dietary composition with BMI in subjects across all age groups. 22,38,39 Our studies also provided strong evidence that when implausible reporting occurs, whole eating occasions are omitted, and reported portion sizes and energy density of both meals and snacks are lower in the total sample compared to the sample limited to plausible reporters. 22,39 Thus, it is not surprising that we observed different relationships of both eating patterns and dietary composition with BMI in our study than have been previously reported, and we recommend that future epidemiological studies on dietary associations with BMI also identify and screen out implausible energy intake reports.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…[67][68][69] In our previous analyses, we showed that including only plausible reports resulted in stronger relationships of both eating patterns and dietary composition with BMI in subjects across all age groups. 22,38,39 Our studies also provided strong evidence that when implausible reporting occurs, whole eating occasions are omitted, and reported portion sizes and energy density of both meals and snacks are lower in the total sample compared to the sample limited to plausible reporters. 22,39 Thus, it is not surprising that we observed different relationships of both eating patterns and dietary composition with BMI in our study than have been previously reported, and we recommend that future epidemiological studies on dietary associations with BMI also identify and screen out implausible energy intake reports.…”
Section: Discussionmentioning
confidence: 61%
“…However, this resulted in non-standardized coding of eating occasions and multiple same meals consumed on the same day. Therefore, as in our previous studies, 22,39 meal coding was standardized so that not more than one each of breakfast, lunch and dinner, but multiple snacks were allowed, as follows.…”
Section: Standardization Of Eating Occasionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the relationship between snack food intake and overweight in children and adolescents produce contradictory results (10)(11)(12)(13)(14)(15)(16)(17) .…”
mentioning
confidence: 99%
“…0 on the natural log scale) were calculated, taking into account coefficients of variation in intakes and other components of energy balance (i.e. the within-subject variation in EI = 23 %; the error in the EER equations = 4·8 %; the day-to-day variation in total energy expenditure = 8·2 %) (52) . Consequently, under-, acceptable and over-reporters were defined as having EI:EER <0·69, 0·69-1·46 and >1·46, respectively.…”
Section: Assessment Of Non-dietary Variablesmentioning
confidence: 99%